A study protocol for a randomised controlled trial evaluating clinical effects of platelet transfusion products: the Pathogen Reduction Evaluation and Predictive Analytical Rating Score (PREPAReS) trial. Issue 1 (27th January 2016) - Ypma, Paula F; van der Meer, Pieter F; Heddle, Nancy M; van Hilten, Joost A; Stijnen, Theo; Middelburg, Rutger A; Hervig, Tor; van der Bom, Johanna G; Brand, Anneke; Kerkhoffs, Jean-Louis H
Abstract : Introduction: Patients with chemotherapy-induced thrombocytopaenia frequently experience minor and sometimes severe bleeding complications. Unrestrictive availability of safe and effective blood products is presumed by treating physicians as well as patients. Pathogen reduction technology potentially offers the opportunity to enhance safety by reducing bacterial and viral contamination of platelet products along with a potential reduction of alloimmunisation in patients receiving multiple platelet transfusions. Methods and analysis: To test efficacy, a randomised, single-blinded, multicentre controlled trial was designed to evaluate clinical non-inferiority of pathogen-reduced platelet concentrates treated by the Mirasol system, compared with standard plasma-stored platelet concentrates using the percentage of patients with WHO grade ≥2 bleeding complications as the primary endpoint. The upper limit of the 95% CI of the non-inferiority margin was chosen to be a ≤12.5% increase in this percentage. Bleeding symptoms are actively monitored on a daily basis. The adjudication of the bleeding grade is performed by 3 adjudicators, blinded to the platelet product randomisation as well as by an automated computer algorithm. Interim analyses evaluating bleeding complications as well as serious adverse events are performed after each batch of 60 patients. The study started in 2010 and patients will be enrolled up to a maximum of 618 patients, depending on the results of consecutive interim analyses. A flexible stopping rule was designed allowing stopping for non-inferiority or futility. Besides analysing effects of pathogen reduction on clinical efficacy, the Pathogen Reduction Evaluation and Predictive Analytical Rating Score (PREPAReS) is designed to answer several other pending questions and translational issues related to bleeding and alloimmunisation, formulated as secondary and tertiary endpoints. Ethics and dissemination: Ethics approval was obtained in all 3 participating countries. Results of the main trial and each of the secondary endpoints will be submitted for publication in a peer-reviewed journal. Trial registration number: NTR2106; Pre-results.